"That's My Life Jacket!" Speculative Documentary as a Counter Strategy to Documentary Taxidermy. Issue 1 (2nd January 2019) - Bellinck, Thomas; van Dienderen, An
ABSTRACT: Despite the socially committed attitude many documentary artists take, documentaries often end up underpinning a large-scale epistemological enterprise linked to global capitalism and Western colonialism (H. Steyerl, "Documentary Uncertainty, " Re-visiones (2011) www.re-visiones.net ). Ai Weiwei's Human Flow (2017), an award-winning documentary about the "refugee crisis", provides an insightful case study. The film's well-intended activism becomes a mere trope that does not prompt any change. The formal strategies deployed do not address the power differentials between the filmmakers and their subjects, so that neither subjects nor viewers are left with any form of agency. In contrast, this article argues for embracing a speculative form of documentary which puts the messiness at its heart that is typical of the relations between representation and reality, between the West and its constructed "others". Acknowledging the impossibility to access the real in an unmediated manner, the authors believe in the intertwining of ethics and form; and in the transformative potential of art. Inspired by the pioneers of documentary art and drawing from their own practice-based research as film and theatre makers, the authors hope to offer an insight into some of the speculative documentary's possible counter-strategies to go against the grain of taxidermic, image-positivist mainstreams.